Recent developments of topoisomerase inhibitors: Clinical trials, emerging indications, novel molecules and global sales - Andrey D. Bondarev; Jörgen Jonsson; Vladimir N. Chubarev; Vadim V. Tarasov; Francisco Alejandro Lagunas-Rangel; Helgi B. Schiöth (Elsevier, 2024)
The nucleic acid topoisomerases (TOP) are an evolutionary conserved mechanism to solve topological problems within DNA and RNA that have been historically well-established as a chemotherapeutic target. During investigation of trends within clinical trials, we have identified a very high number of clinical trials involving TOP inhibitors, prompting us to further evaluate the current status of this class of therapeutic agents. In total, we have identified 233 unique molecules with TOP-inhibiting activity. In this review, we provide an overview of the clinical drug development highlighting advances in current clinical uses and discussing novel drugs and indications under development. A wide range of bacterial infections, along with solid and hematologic neoplasms, represent the bulk of clinically approved indications. Negative ADR profile and drug resistance among the antibacterial TOP inhibitors and anthracycline-mediated cardiotoxicity in the antineoplastic TOP inhibitors are major points of concern, subject to continuous research efforts. Ongoing development continues to focus on bacterial infections and cancer; however, there is a degree of diversification in terms of novel drug classes and previously uncovered indications, such as glioblastoma multiforme or Clostridium difficile infections. Preclinical studies show potential in viral, protozoal, parasitic and fungal infections as well and suggest the emergence of a novel target, TOP IIIβ. We predict further growth and diversification of the field thanks to the large number of experimental TOP inhibitors emerging.